Immunohistochemical Expression Profile of P16 In Cervical Carcinoma Patients At Siloam Mrccc Cancer Hospital In 2022 - Ani Oranda Panjaitan; Fajar Lamhot Gultom; Clariza Ovelyn Iona Rombe (CV. Inara, 2026)
Cervical carcinoma is a rapidly growing health issue, with global cases reaching 662,301 and causing 348,874 deaths in 2022. Almost all cervical carcinoma cases are associated with persistent Human Papillomavirus (HPV) infection. The cell cycle-dependent kinase inhibitor (p16) serves as a reliable surrogate biomarker for HPV-associated cervical carcinoma. This descriptive observational study analyzes the dataset from the academic file